Generative Artificial Intelligence Integration for the Education of Islamic Communication and Broadcasting - Hartati, Rahmi; Fujiantie, Jerina; Ries Dyah Fitriyah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This research aims to explore the use of Generative Artificial Intelligence (AI) in lectures, examine the changes in learning culture and its impacts, and provide recommendations for optimizing the integration of Generative AI for students of Islamic Communication and Broadcasting at UIN Antasari Banjarmasin. The study involves lecturers and students as research subjects. Data collection techniques include in-depth interviews and documentation. The findings have revealed that students’ use of Generative AI for completing academic assignments has led to significant changes in lecture culture and dynamics. Students have become more active in asking questions and engaging in discussions. However, the use of Generative AI also presents various challenges and negative impacts, such as a decline in literacy skills and critical thinking. Therefore, it is crucial to provide lecturer guidance and mentorship, training on AI utilization, and policies that encourage collaboration between traditional and modern learning approaches.